Not Above the Law: A Legal and Ethical Analysis of Short-Term Experiences in Global Health - Virginia Rowthorn (Ubiquity Press, 2019)
Background: Persons from high-income countries have multiple opportunities today to participate in “short-term experiences in global health” (STEGHs) in low-resourced countries. STEGHs are organized through religious missions, service learning, medical internships, global health education, and international electives. An issue of increasing concern in STEGHs is “hands-on” participation in clinical procedures by volunteers and students with limited or no medical training. To address these concerns, best practices and ethical standards have been developed. However, not all STEGH organizations adhere to these guidelines, and some actively or tacitly allow unethical and potentially illegal practices. Objectives: This paper considers the legal framework within which STEGHs operate. It assesses whether certain STEGH practices break laws in the US and/or host countries or violate international “soft” legal norms. Two activities of particular concern are: practicing medicine without a license and drug importation and distribution. Conclusions: Many activities undertaken in STEGHs would be illegal if they took place on US soil. In addition, these same activities are often illegal in the host countries where STEGHs operate, although compliance is unevenly enforced. Many STEGH activities violate World Health Organization guidelines for ethical conduct in humanitarian activities. Recommendations: This paper encourages STEGH organizations to end unethical and potentially illegal activities; urges regulatory and non-regulatory stakeholders to alter policies that motivate participation in illegal or unethical STEGH activities; and encourages host countries to enforce their local and national health laws.